PENGARUH IMPLEMENTASI KEBIJAKAN PEMBELAJARAN ONLINE TERHADAP PRESTASI BELAJAR SISWA DI SEKOLAH DASAR NEGERI 103 KECAMATAN MAPANGET KOTA MANADO - HARIANTO, LA HAI ROI RUMBAYAN; RARES, JOYCE JACINTA; TAMPONGANGOY, DEYSI LIVI (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study was to determine the effect of the implementation of online learning policies on student achievement in State Elementary School 103, Mapanget District, Manado City. This research uses quantitative research. The population and samples used were teachers and students in Grades 4-6 at the State Elementary School 103, Mapanget District, Manado City. The data collection techniques in this study were questionnaires, observations, literature studies and documentation. The sample used in this study was 60 student respondents from grades 4-6 SD. Data collection was carried out by running a questionnaire. Based on the results in this study, it showed that the implementation of online learning policies had a significant effect on student learning achievement, namely 44.6% and 55.4% influenced by other factors. the most supportive indicator is the readiness of educator resources, from the results of the research the teacher is able to prepare everything before starting learning moreover the teacher is able to master the technology that will be used in online learning activities in the form of google meet or zoom meetings, so that students can easily follow each lesson given by the teacher even though online, although there are obstacles encountered, namely students do not have smartphones, there is no parental assistance in learning activities and there are even students who do not have internet data to participate in online learning. Â Â Keywords: Policy Implementation, Learning Achievemen